What are the key leadership competencies required by medical school deans in Uganda? A qualitative cross-sectional study. - Kyamanywa, Patrick; Redding, Peter (African Health Sciences, 2021)
Background: Effective leadership is vital for organizational growth and sustainability. Globally, medical schools are faced with leadership challenges due to the pace of globalization, technological advances, reduced funding and changed funding cycles, increasing student enrolment, demands of accreditation, academic collaboration, innovations and research. This makes identification and selection for the right leadership competencies a priority. Objectives: To investigate the key leadership competencies required by deans of medical schools in Uganda. Method: A qualitative study using semi-structured interviews with the current deans and purposively selected former deans of medical schools in Uganda was conducted between March and June, 2020. We analysed the data using Grounded theory. Results: Thirteen (13) deans (9 of the 12 current deans and 4 former deans) participated in the study. We established ten (10) key roles of a dean of a medical school categorised as academic leadership, administrative leadership and professional leadership. Eleven (11) key competencies were identified as necessary for effective leadership of medical schools in Uganda, and categorized as personality-related competencies, organizational management competencies and medical/health expertise. Conclusions: A dean of a medical school in Uganda should possess a combination of personality, medical expertise, health professions training and organizational management competencies and have training in leadership, financial and resources management.
Keywords: Competencies; Dean; effective leadership; medical schools